GORELOVSKY VOLCANIC CENTER, SOUTH KAMCHATKA: STRUCTURE AND EVOLUTION - Selyangin O.B.; Ponomareva V.V. (My University, 1999)
Gorelovsky volcanic center is localized in the area of a high negative gravity anomaly. Its volcanic history included the growth of a pre-caldera dacite-andesite cone, the formation of a large caldera as a result of the eruption of > 100 km3 of ignimbrite and pumice, subcircular multivent dacite-basalt volcanism, and the growth of the present-day Gorelyi basalt cone inside the caldera with a rift system on it. The results of detailed geological, volcanological, and tephrochronologic studies revealed the evolution trend of the center and its magma system which had evolved from a deep large central-type magma source to a small shallow, fissure-and central-type system with the increasing amount of basalts in the eruption products.